(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article analyzes the peculiarities of creating the theme of the Little Man in the works of V. M. Shukshin in terms of traditions and innovation. The peculiarities of his poetics, the originality of the author’s interpretations